Investigation of Premixed Combustion Properties of Gaseous Fuel (LPG, Propane, & Butane) in Tubular Burner - Jasem M. Abdul Kareem al-Jaff (Tishreen University, 2016)
In the present research, the propagation properties of premixed combustion at high stability has been investigated using three types of hydrocarbon fuels (LPG, C3H8, and C4H10) in a tubular burner.Experimental work has been carried out for laminar fuel-air mixture. Bunson burner methods were introduced for designing and manufacturing of integrated combustion system to get a wide range of equivalence ratio introducing all the reactance in combustion process, computed and increase the range efficiency of combustion stability to (ζs=9.33%), reducing losses in dead space zone, and reducing emissions products by reducing the emission of (NOX,CO). The laminar burning velocity has been computed using two techniques based on flame frontal surface area and angle of frame front with aid of data image of flame front at atmosphere pressure andTu=300K for a range of equivalence ratio             (0.7< Φ<1.5). Comparison of results with previous literature showed good agreement with the present work. في البحث الحالي درست خصائص انتشار اللهب مسبق الخلط في شروط الاستقرارية العالية وذلك  باستخدام ثلاث أنواع من الوقود الهيدروكربوني (LPG ، بروبان ، بيوتان) في الحراق الأنبوبي  (Tubular Burner) ، وأجريت الدراسة التجريبية في شروط الجريان الصفائحي للوقود والهواء. تم تصميم وتصنيع حراق بنسن ومنظومة احتراق متكاملة ومميزة للحصول على مديات واسعة للنسبة المكافئة (ϕ) ومشاركة كافة الخليط في الاحتراق وزيادة كفاءة استقرارية الاحتراق الى (%9.33=Sζ) وتقليل الخسائر في منطقة الحيز الميت، والحد من انبعاث نواتج الاحتراق بتقليل قيمة انبعاث غاز أول أوكسيد الكربون (CO  و NOX) السامة في المحيط الخارجي. ان سرعة انتشار اللهب الصفائحي (Su) تم حسابها اعتماداَ على تقنيتي (الزاوية والمساحة) والبيانات المستحصلة من صور جبهة اللهب والمأخوذة بطريقة التصوير المرئي عند الظروف المختبرية (Tu=300 K ، Pu= 1 atm) ولمدى من النسب المكافئة (1.5 ˂ϕ˂ 0.7 (. تم مقارنة النتائج المستخلصة مع نتائج البحوث المنشورة لسرعة انتشار اللهب وقد ظهر هناك اتفاق جيد بينهما.